The effects of inorganic and organic Zn, Cu and Mo supplementation to the in vitro digestibility of Elephant grass were studied in this trial. The in vitro trial used the TILLEY dan TERRY method modified by VAN SOEST with the incubation of the grass for 4 - D, Yulistiani; Gallagher, J.R; Barneveld, R. Van (Indonesian Journal of Animal and Veterinary Sciences, 2000)
chemical composition (nitrogen/N; neutral detergent tibre/NDF; acid detergent fibre/ADF; hemicellulose/HC; lignin and silica) and IVOMD (in vitro organic matter digestibility). Straws from eight varieties obtained from Yanco Agricultural Institute, Leeton, N.S.W. was used. Straws were cut into upper and lower part in equal length, then chopped. Chopped straw from each varieties and each part was treated with urea at 4% DM. The experiment used an 8x2x2 factorial design. Results showed that the chemical composition and IVOMD varied between varieties. Before treatment with urea, in all varieties the N content was higher in the upper (8.1-11.1 g/kg) than the lower part (5.8-8.3 g/kg). The IVOMD of the lower part was higher than that of the upper part except for lIb, and Yrl varieties. The IVOMD of the lower part untreated straw ranged from 325 - 498 g/kg whereas in the upper part it ranged from 325-439 g/kg. Urea treatment consistently increased the N content and IVOMD of both parts in all varieties. After urea treatment there was no significant difference in IVOMD between upper and lower part in any variety. The increase of IVOMD in response to urea treatment was higher when the original quality of straw is low where the increase IVOMD is 53% (from 325 to 499 g/kg). There was no consistent effect of urea treatment on the other chemical components. This study concluded that the urea treatment would be more beneficial for use with low quality rice straw. Â  Key words: Rice straw, variety, urea treatment, chemical composition, in vitro organic matter digestibility